PROPOSED INTEGRATED LISTENING AND SPEAKING SKILLS LEARNING ACTIVITIES USING PROJECT BASED LEARNING MODEL - Indriani, Ketut Santi (Premise: Journal of English Education and Applied Linguistics, 2024)
This study explores the development of project-based learning activities tailored for the integration of listening and speaking skills in an EFL context. Listening skills, in particular, present challenges for educators, who often struggle to modify traditional instructional methods. Conventional approaches to listening instruction, such as listening to audio and answering questions, tend to be monotonous, potentially diminishing student motivation, especially in English language learning. To address these issues and enhance student competence, integrating listening and speaking skills through a project-based learning (PBL) approach has been recommended (Loi & Hong, 2023a). The design of these activities and projects must be carefully crafted to ensure effective learning outcomes and improvement in both skill areas. This study adopts a literature review methodology to identify suitable forms of project-based learning activities for integrating listening and speaking skills. The data were gathered from existing studies and analyzed using data reduction techniques, focusing on key insights, which were then synthesized into a narrative that outlines a project-based learning plan. The results of the research provide a detailed series of integrated activities aimed at enhancing both listening and speaking skills, culminating in a final project involving the creation of a short video. The designed activities were found to significantly boost student motivation and participation throughout the learning process.